Analisis Kritis Terhadap Pemikiran Utilitarianisme Jeremy Bentham dalam Perspektif Etika dan Filsafat Manusia - Rahman, Ayi; Maulana, Muhammad Falikh Rifqi (Medpro, 2023)
Utilitarianism, introduced by Jeremy Bentham in the 18th century, proposes that the moral correctness of actions is judged on the basis of consequences that result in maximum happiness or well-being for the individuals involved, known as